A Study on Integrated Structure and QoS Policy for Heterogeneous Military Transports - Park, Gyudong; Lee, Gyu Min; Roh, Byeong Hee; Kim, Euikook; Ryu, Dong Kuk (Journal of Korean Institute of Communications and Information Sciences, 2020)
Korean military is using several heterogeneous transports and it is expected to improve the efficiency, survivability and security of the transports. This paper analyzes the status of implementation and operation of the transports, and proposes an integrated structure and QoS policy for the heterogeneous transports as improvement measures to satisfy the customer’s requirements and solve the problems. And shows the feasibility and superiority of the proposed integrated structure and QoS policy through experiments.
Keywords: DoDIN; Heterogeneous Transports; Integrated Structure; MPTCP; QoS